Identification and comparative analysis of seed storage proteins (SSPs) in sequenced cereal genomes - Chandni (My University, 2022)
Seeds are not only propagation and dispersal organs, but they also synthesise and store proteins known as seed storage proteins (SSPs). The high protein content of the plant can be mobilised and utilised for plant care, defence, and growth. Because of their high quality and quantity, SSPs are utilised in food all around the world. SSPs perform a key metabolic and structural role in seeds, storing nitrogen, carbon, and energy during germination. These storage proteins share several characteristics such as they are synthesised in high concentrations in specific tissues during germination and at certain stages of plant development and gets deposited in the form of protein bodies and can be mobilised for seed defence. Various computational and experimental methods are used to identify seed storage proteins and understand its function by in depth annotation studies. In this study, SSPs were identified and analysed in sequenced cereal genomes using various bioinformatics tools
Keywords: Seed Storage Proteins; Homology Searches; Annotation; MEGA; HMMER Software